Salinity induced changes in cotton (Gossypium hirsutum L.) - (:unkn) unknown (My University, 2012)
Cotton (Gossypium hirsutum L.) is susceptible to abiotic stresses. High salinity is a common abiotic stress condition that adversely affects plant growth. Altered ion and water homeostasis changes due to NaCI stress, lead to molecular damage, growth arrest and even death. As a consequence of salt stress effects, secondary stresses such as oxidative damage by reactive oxygen species may occur. Reactive oxygen species can alter cellular metabolism through oxidative damage of lipids, proteins and nucleic acids causing lipid peroxidation, protein denaturing and DNA mutation. In recent years, several selective and sensitive assays have been developed to evaluate the effects of environmental stress on vegetal organisms. RAPD is one of them and developed for DNA analysis. In this study, cotton seedlings were used as bioindicator of salinity stress in the range of 50-400 mM. Effects of salinity stress were determined by comparing RAPD profiles of normal and treated cotton seedlings include variations in band intensities as well as gains or losses of band numbers. The DNA polymorphisms detected by RAPD analysis could be used as an investigation tool and useful biomarker assay for observing environmental stresses such as high salinity on vegetal organisms.